Wide bandwidth microstrip antenna with defected patch surface for low cross polarization applications. Issue 8 (16th May 2017) - Ghosh, Abhijyoti; Chattopadhyay, Sudipta; Singh, L. Lolit Kumar; Basu, Banani
Abstract: A simple and single element wide slot dipole loaded shorted rectangular microstrip antenna has been proposed and investigated experimentally for broad impedance bandwidth and improved cross polarized (XP) radiation compared to maximum co‐polarized (CP) gain without changing the co‐polarized (CP) radiation pattern. Around 23‐35 dB isolation between CP and XP radiation along with 25% impedance bandwidth is achieved with the proposed structure. The measured gain of the antenna is around 6.2 dBi over the entire band. The present antenna is very simple and easy to manufacture. Unlike the other structures, the present one is free from back radiation in terms of XP fields. The design of the antenna structure is theoretically justified and rigorously analyzed. The present investigation provides an insightful, clear visualization‐based understanding of the concurrent improvement in both the impedance bandwidth and XP performance with the present structure.